Animal Diary: The Design and Development of a Game Application to Enhance Early Primary School Children’s Attention - Permsawadchai, Suratanakorm; Songwichai, Kanokon; Punchoojit, Lumpapun (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
Attention is a fundamental component of academic achievement, as it allows children to concentrate on tasks, filter out distractions, and process information efficiently. This article presents an academic discussion on the development and design of Animal Diary, a smartphone-based digital game specifically designed to enhance selective attention in early primary school children. The discussion emphasizes the game’s conceptual framework and implementation process. Animal Diary integrates principles from cognitive psychology and child-computer interaction (CCI) to provide an engaging, developmentally appropriate experience that supports attention training in young learners. "Animal Diary" consists of three mini-games—Crocodile Dentist Roulette, Egg Chess, and Cooking Matching—each designed to challenge and improve children’s ability to maintain focus. The game incorporates intuitive controls, a progressive challenge system, real-time feedback, and reward-based mechanics to sustain engagement and motivation. Developed using Unity, the application features a pixel art aesthetic and an interface optimized for young users, ensuring usability and eye-pleasing. The conceptual design of the game was refined through interview sessions with primary school teachers, who provided insights and feedback on the developmental appropriateness and educational value of the game content. The feedback was positive, supporting the game’s relevance for the target age group. In addition, a pilot test was conducted with two early primary school children to assess the game’s usability and engagement. The results were positive, indicating that the games captured attention and maintained user interest.